Aquilombamento da saúde mental: práticas de cuidado com e para mulheres negras - Barbosa, Eliane Clares (2024)
The imagery constructed around the word gender points to a naturalized understanding of the way of being a man/woman. In this context, marked historically and culturally, subjects assume different ways of subjectifying themselves. Therefore, to be better understood, gender needs to be linked to other markers such as race. This allows women's experience not to be understood as universal, but crossed by practices such as racism. The main objective of this work was to identify mental health care practices for black women. This was an intervention research in which data collection was carried out between April 2023 and February 2024, in three distinct stages: i) holding workshops on gender, race and mental health with users of therapeutic groups a Psychosocial Care Center (CAPS); ii) carrying out an individual interview, using a semi- structured script and a socioeconomic and professional training questionnaire with professionals from a general CAPS and an alcohol and other drug CAPS; and iii) holding a mini-course on gender, race and mental health with mental health equipment professionals. Data analysis was carried out through the theoretical-methodological approach of the notion of discursive practices and production of meanings and, also, of black feminism. The importance of commitment to professional training for racial issues was then highlighted, as well as the fight against racial invisibilization in public health policies, establishing heterogeneous forms of care, which enable a comprehensive approach to the person. The construction and experience of this research, in addition to highlighting the need for a long journey towards racial and gender equity in mental health, points to fertile ground in the search for care centered on the person and their needs.